Nucleoside-2′, 3′/3′, 5′-bis(thio)phosphate antioxidants are also capable of disassembly of amyloid beta42-Zn(ii)/Cu(ii) aggregates via Zn(ii)/Cu(ii)-chelation. Issue 20 (25th April 2016) - Hevroni, Bosmat Levi; Major, Dan Thomas; Dixit, Mudit; Mhashal, Anil Ranu; Das, Susanta; Fischer, Bilha
Abstract : Nucleoside-2′, 3′/3′, 5′-bis(thio)phosphate antioxidants were identified as efficient agents of disassembly of Aβ42 -Zn(ii )/Cu(ii ) aggregates by M(ii )-chelation, thus making promising scaffolds for new Alzheimer's disease therapeutics. Abstract : Currently, there is an urgent need for biocompatible metal-ion chelators capable of antioxidant activity and disassembly of amyloid beta (Aβ)-aggregates as potential therapeutics for Alzheimer's disease (AD). We recently demonstrated the promising antioxidant activity of adenine/guanine 2′, 3′ or 3′, 5′-bis(thio)phosphate analogues, 2′-dA/G3′5′PO/S and A2′3′PO/S, and their affinity to Zn(ii )-ions. These findings encouraged us to evaluate them as agents for the dissolution of Aβ42 -Zn(ii )/Cu(ii ) aggregates. Specifically, we explored their ability to bind Cu(ii )/Zn(ii )-ions, the geometry and stoichiometry of these complexes, Cu(ii )/Zn(ii )-binding-sites and binding mode, and the ability of these analogues to dissolve Aβ42 -Zn(ii )/Cu(ii ) aggregates, as well as their effect on the secondary structure of those aggregates. Finally, we identified the most promising agents for dissolution of Aβ42 -Zn(ii )/Cu(ii ) aggregates. Specifically, we observed the formation of a 1 : 1 complex between 2′-dG3′5′PO and Cu(ii ), involving O4 ligands. Zn(ii ) was coordinated by both thiophosphate groups of 2′-dA3′5′PS and A2′3′PS involving O2S2 ligands in a 1 : 1 stoichiometry. A2′3′PS dissolves Aβ42 -Zn(ii ) and Aβ42 -Cu(ii ) aggregates as effectively as, and 2.5-fold more effectively than EDTA, respectively. Furthermore, 2′-dG3′5′PS and A2′3′PS reverted the Aβ42 -M(ii ) structure, back to that of the free Aβ42 . Finally, cryo-TEM and TEM images confirmed the disassembly of Aβ42 and Aβ42 -M(ii ) aggregates by A2′3′PS. Hence, 2′-dG3′5′PS and A2′3′PS may serve as promising scaffolds for new AD therapeutics, acting as both effective antioxidants and agents for solubilization of Aβ42 -Cu(ii )/Zn(ii ) aggregates.